1966
DOI: 10.1037/h0023579
|View full text |Cite
|
Sign up to set email alerts
|

Changes in self-concepts during group psychotherapy as a function of alternate sessions and vicarious therapy pretraining in institutionalized mental patients and juvenile delinquents.

Abstract: The present study attempted to evaluate the effects of alternate sessions and vicarious therapy pretraining (VTP) in connection with time-limited group psychotherapy in 4 groups each of institutionalized juvenile delinquents and hospitalized mental patients. Ss were administered self-and ideal-self-concept Q sorts pre-and posttherapy. The findings were as follows: (a) the use of alternate sessions did not facilitate improvement in self-and ideal-self-concepts, but effected negative changes in self-concept as c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

1967
1967
1999
1999

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…Of the five studies reviewed in Table 1 that examined effects of vicarious therapy pretraining, only one (France & Dugo, 1985) reported findings on attendance and dropout rates; clients receiving preparation had higher attendance rates relative to clients in the control condition, but similar dropout rates. Several other studies found that pretrained clients had improved treatment process and/or outcome (e.g., Truax et al, 1968;Truax, Wargo, Carkhuff, Kodman, & Moles, 1966), although several other studies did not (e.g., France & Dugo, 1985;Truax & Wargo, 1969). In total, this relatively small body of literature suggests that this technique has at least the potential for positively affecting treatment attendance, process, and outcome.…”
Section: Psychotherapy Preparatory Techniquesmentioning
confidence: 97%
“…Of the five studies reviewed in Table 1 that examined effects of vicarious therapy pretraining, only one (France & Dugo, 1985) reported findings on attendance and dropout rates; clients receiving preparation had higher attendance rates relative to clients in the control condition, but similar dropout rates. Several other studies found that pretrained clients had improved treatment process and/or outcome (e.g., Truax et al, 1968;Truax, Wargo, Carkhuff, Kodman, & Moles, 1966), although several other studies did not (e.g., France & Dugo, 1985;Truax & Wargo, 1969). In total, this relatively small body of literature suggests that this technique has at least the potential for positively affecting treatment attendance, process, and outcome.…”
Section: Psychotherapy Preparatory Techniquesmentioning
confidence: 97%
“…Truax and his associates have carried out a number of studies using the alternate session technique (Truax and Wargo, 1969;Truax et al, 1966;Truax et al, 1970). In only one of their published studies did these researchers find even slightly positive results, and this was a study involving mainly a mildly disturbed, outpatient group of college students (Truax and Wargo, 1969).…”
Section: In the Predicted Direction (Positive)mentioning
confidence: 93%
“…Other supportive forces were the treatment of the subjects by professional personnel and other staff and a positive atmosphere in the institution. In studies successful, the institution was a juvenile detention home (Truax et al, 1966(Truax et al, , 1970, and other institutions in which the subjects might not have had an especially supportive environment outside the leaderless group (Seligman and Sterne, 1969). …”
Section: In the Predicted Direction (Positive)mentioning
confidence: 99%
“…Modeled self-disclosure was found to foster the desired verbal behavior either by itself (Jourard & Friedman, 1970;Rappaport, Gross, & Leppcr, 1973;Stone & Gottlieb, 1975;Stone & Stebbins, 1975) or in combination with specific instructions defining self-disclosure (Stone & Gottlieb, 1975;Whalen, 1969). Truax, Wargo, Carkhuff, Kodman, and Moles (1966) found that the use of an audiotapc taken from interviews as a method of vicarious, therapy pretraining was associated with positive changes in self-concept. Overall, modeled self-disclosure Requests for reprints should be sent to Lewis J. Ellenhorn, Pitzer College, Claremont, California 91711.…”
mentioning
confidence: 99%